Compiling Electronic Shopping Strategy By ES-Test: An Application Of Malaysian Airline Ticket - -, Javad Sadeghzadeh Biglari (2008)
This study proposed to investigate determinants of potential of online sales. We identified three factors namely attitude towards online shopping, familiarity and confidence, and product type.